Quantitative systematic review of randomised controlled trials comparing antibiotic with placebo for acute cough in adults - Fahey, Tom (British Medical Journal, 1998)
Objectives: To assess whether antibiotic treatment for acute cough is effective and to measure the side effects of such treatment. Design: Quantitative systematic review of randomised placebo controlled trials. Data sources: Nine trials (8 published, 1 unpublished) retrieved from a systematic search (electronic databases, contact with authors, contact with drug manufacturers, reference lists); no restriction on language. Main outcome measures: Proportion of subjects with productive cough at follow up (7-11 days after consultation with general practitioner); proportion of subjects who had not improved clinically at follow up; proportion of subjects who reported side effects from taking antibiotic or placebo. Results: Eight trials contributed to the meta-analysis. Resolution of cough was not affected by antibiotic treatment (relative risk 0.85 (95% confidence interval 0.73 to 1.00)), neither was clinical improvement at re-examination (relative risk 0.62 (0.36 to 1.09)). The side effects of antibiotic were more common in the antibiotic group when compared to placebo (relative risk 1.51 (0.86 to 2.64)). Conclusions: Treatment with antibiotic does not affect the resolution of cough or alter the course of illness. The benefits of antibiotic treatment are marginal for most patients with acute cough and may be outweighed by the side effects of treatment.